Answer:
<u><em>y = 63</em></u>
Step-by-step explanation:
<em>y is directly proportional to x²</em>
<em>As given,</em>
<em>when y = 3 => x = 2</em>
<em>So, 3 = 4 - 1</em>
<em>Which means the relation can be written as :-</em>
<em>y = x² - 1</em>
<em></em>
<em>Substituting x = 8</em>
<em>y = (8)² - 1</em>
<em>y = 64 - 1</em>
<u><em>y = 63</em></u>
<h3><em>1st quadrant,</em></h3><h3><em>(+,+) in 1st quadrants </em></h3><h3><em>HOPE IT HELPS !!!</em></h3>
Answer:
she owes nothing and the credit card company owes her nothing.
Add 11.7 and 2. The answer is 13.7 (quarts).
Answer:
The solution isn't listed
Step-by-step explanation:
x = 6 because you add -10 to -4 and you get 6